2015
DOI: 10.1089/cyber.2015.0063
|View full text |Cite
|
Sign up to set email alerts
|

Addiction and Engagement: An Explorative Study Toward Classification Criteria for Internet Gaming Disorder

Abstract: The DSM-5 introduced Internet gaming disorder (IGD) as a condition needing more research. Proposed criteria include tolerance, preoccupation, deceiving, or continued excess despite psychosocial problems. However, studies suggest differences between addicted and engaged players. Therefore, this study investigated differences between engagement and addiction in a German-speaking sample of expert World of Warcraft players. Using an online-based questionnaire, 682 participants were surveyed (Mage=23.26 years; 84.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
45
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 48 publications
5
45
0
6
Order By: Relevance
“…Lehenbauer-Baum et al . [29] reported that addicted gamers have a higher association with psychopathologies than controls. They found that addicts scored higher in Beck's Depression Inventory and Social Phobia Inventory and are less agreeable, thorough, and emotionally less stable.…”
Section: Comorbidities Associated With Internet Gaming Addictionmentioning
confidence: 99%
“…Lehenbauer-Baum et al . [29] reported that addicted gamers have a higher association with psychopathologies than controls. They found that addicts scored higher in Beck's Depression Inventory and Social Phobia Inventory and are less agreeable, thorough, and emotionally less stable.…”
Section: Comorbidities Associated With Internet Gaming Addictionmentioning
confidence: 99%
“…Although the positive effects of health gaming have been demonstrated by a large body of research, [1][2][3][4] numerous studies have systematically reported potentially harmful effects games can have on human health due to its potentially addictive properties [5][6][7] and overall detrimental effects [8][9][10][11] in several life domains for a minority of gamers. Such harmful effects related to addiction to gaming can include decreased levels of exercise and sports, 12 impaired decision-making, 13 poorer psychosomatic health, 14 greater incidence of psychiatric symptoms, 15 lower expected college engagement and grades in adolescent students, 5 compromised prefrontal cognitive control over emotional interference, 16 in addition to other psychiatric disorders and abnormal behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroticismo é o fator que correlaciona mais fortemente com satisfação de vida e afetos negativos, enquanto extroversão relaciona-se com os afetos positivos (Anglim & Grant, 2016). Alguns pesquisadores investigam as relações do bem-estar e fatores de personalidade com o engajamento a certas atividades, como o uso de jogos eletrônicos (Lehenbauer-Baum et al, 2015;Braun, Stopfer, Müller, Beutel, & Egloff, 2016;Jimenez et al, 2019).…”
unclassified
“…Pesquisadores apontaram correlações positivas, negativas ou inexistentes entre as variáveis de bem-estar e as horas de jogo (Comello et al, 2016;Carras et al, 2017;Allen & Anderson, 2018). A personalidade dos jogadores também foi alvo de investigações (Lehenbauer-Baum et al, 2015;Braun et al, 2016;Jimenez et al, 2019). Em pessoas que reportaram sintomas de transtorno do jogo pela internet, neuroticismo se mostrou mais alto, enquanto realização, abertura, extroversão e amabilidade obtiveram escores mais baixos (Lehenbauer-Baum et al, 2015;Braun et al, 2016).…”
unclassified
See 1 more Smart Citation